2021
DOI: 10.1177/03064190211026229
|View full text |Cite
|
Sign up to set email alerts
|

Student-led development of a lightboard to enhance future student learning

Abstract: Lightboards are emerging technologies, helping to optimize online and flipped classroom environments by enabling the instructor to face the audience while writing on a transparent board. Although both commercial and do-it-yourself designs of lightboards are currently available, we have conducted a student-led engineering research and design project to optimize a lightboard design for broader use on campus to enhance the learning of future students. Through systematic side-by-side comparison, the team determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Three studies (Fiorella & Mayer, 2016, Experiments 1 & 2; Fiorella et al, 2019, Experiment 1) reported that instructors' drawing on a whiteboard while explaining or demonstrating a science topic led to higher retention or transfer scores than showing already-drawn visuals. Moreover, in one study (Swenson et al, 2021), most students favored hand-written content rather than pre-written content. Signaling, temporal contiguity, and segmenting principles of multimedia learning explain why observing instructor drawing can be better for learning (Fiorella & Mayer, 2016).…”
Section: Generative Activitiesmentioning
confidence: 96%
“…Three studies (Fiorella & Mayer, 2016, Experiments 1 & 2; Fiorella et al, 2019, Experiment 1) reported that instructors' drawing on a whiteboard while explaining or demonstrating a science topic led to higher retention or transfer scores than showing already-drawn visuals. Moreover, in one study (Swenson et al, 2021), most students favored hand-written content rather than pre-written content. Signaling, temporal contiguity, and segmenting principles of multimedia learning explain why observing instructor drawing can be better for learning (Fiorella & Mayer, 2016).…”
Section: Generative Activitiesmentioning
confidence: 96%
“…Pal et al, 2020). Seeing the teacher's face and handwriting the information generates greater receptivity in the students (Swenson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%